MARINE CAPTURE FISHERIES POLICY FORMULATION AND THE ROLE OF MARINE PROTECTED AREAS AS TOOL FOR FISHERIES MANAGEMENT IN INDONESIA - Wiadnya, D. G.R.; Mous, P. J.; Djohani, R.; Erdmann, M. V.; Halim, A.; Knight, M.; Pet-Soede, L.; Pet, J. S. (Marine Research in Indonesia, 2006)
The FAO Code of Conduct for Responsible Fisheries states that conservation and management decisions for fisheries should be based on the best scientific evidence available. Studies show that most of Indonesias capture fisheries are either full or over-exploited. However, the fishery sector is still expected to contribute to the increase of Indonesias GNP through an increase in total catches. Furthermore, the current practice of using catch-effort data and Maximum Sustainable Yield models to inform Indonesiaâs fisheries policies is flawed, putting sustainability and long-term profitability of Indonesias fisheries at risk. In this paper, the authors argue that to ensure the survival of Indonesias fish stocks and fisheries: fisheries policy must shift from development-oriented management towards management for sustainability. Furthermore, fisheries managers must accept that untapped resources may not exist or cannot be exploited profitably, and that any transfer of fishing effort between fishing grounds may contribute to collapse of local fisheries. Also, fisheries managers should change the management paradigm from MSY models to eco-system based management, wherein Marine Protected Areas should play an important role.